2015
DOI: 10.1262/jrd.2015-024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the global gene expression profiles in the bovine endometrium between summer and autumn

Abstract: Heat stress compromises fertility during summer in dairy and beef cows by causing nutritional, physiological and reproductive damages. To examine the difference in endometrial conditions in cows between summer and autumn, gene expression profiles were compared using a 15 K bovine oligo DNA microarray. The trial was conducted in the summer (early in September) and autumn (mid-November) seasons of two consecutive years (2013–2014) in Morioka, Japan. Endometrial samples were collected from the cows using a biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
4
12
0
1
Order By: Relevance
“…The high expression of CALPR in the MRB duodenum, on the other hand, suggested an inflammation state (46) and an increased intestinal permeability induced by heat stress which is supported in our experimental conditions by higher serum concentrations of FITC-D. Furthermore, the down regulation of jejunal CDH1 and ileal ZO-1 expression continue to support that heat stress induce intestinal epithelial barrier dysfunction in MRB birds (47)(48)(49)(50).…”
Section: Discussionsupporting
confidence: 80%
“…The high expression of CALPR in the MRB duodenum, on the other hand, suggested an inflammation state (46) and an increased intestinal permeability induced by heat stress which is supported in our experimental conditions by higher serum concentrations of FITC-D. Furthermore, the down regulation of jejunal CDH1 and ileal ZO-1 expression continue to support that heat stress induce intestinal epithelial barrier dysfunction in MRB birds (47)(48)(49)(50).…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies have also investigated gene expression profiles under various conditions of the bovine endometrium during the estrous cycle and/or during early pregnancy using DNA microarray or RNA sequencing [1118]. In addition, microarray studies have revealed that heat stress and steroid hormones directly affect bovine endometrial gene expression profiles [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Due to the limited supply of nonhuman primate oocytes, this hypothesis was not tested in the present study. However, NTS expression has been reported in the mammalian reproductive tract, including follicular granulosa cells (28), uterus (3,4,29) and oviduct (3,4,30). Neurotensin expression by cumulus cells was reported for mouse cells (3) but not bovine cells (5), so species differences may exist.…”
Section: Discussionmentioning
confidence: 99%